Study on irrigation systems rehabilitation and improved operations and management: Final report for ADB Regional Technical Assistance 5273 - International Irrigation Management Institute (International Irrigation Management Institute, 1989)
Vol. 1 - Activity A: Rehabilitation and improvement for management; Vol 2 - Activity B: Dry season irrigation management for rice based systems; Vol. 3 - Activity C: Financing the cost of irrigation.